Carbon storage and forest fire influences in tropical rainforests - Lackmann, Steffen (2011)
Deforestation and degradation account for nearly 20 percent of global greenhouse gas emissions today – playing a key role in the complex system of climate change. Most deforestation is undertaken in developing countries, resulting in loss of biodiversity and livelihoods for millions of people and animals. With an increasing recognition of this problem the term REDD (Reducing Emissions from Deforestation and Degradation) emerged during the last years. The basic idea behind a REDD regime is that developing countries receive financial incentives for preventing further deforestation to protect the worldwide climate. Whereas afforestation and reforestation projects were included in the initial Kyoto Protocol, REDD was only eligible for the voluntary carbon market, where criteria and best guidance for these project types were developed and where some avoided deforestation projects were implemented. One of these projects was the “Avoided Deforestation Project in the Sierra del Lacandón National Park”, placed in the Maya Biosphere Reserve in Northern Guatemala. The company Carbon Decisions International was selected to create a deforestation model for the reference region of Petén. Within this context the objective of this thesis was to analyze the effects of forest fires on carbon stocks in the study area and to analyze which carbon pools were specifically affected by the fires. Furthermore, a close look on the regeneration of forests after fire was taken in order to better understand how carbon stocks recreate after disturbance regimes.